Repair of Incisional Hernia by Component Separation Technique & Pre-Peritoneal Mesh Placement-Initial Outcome (Journal of Surgical Sciences, 2021)
Background: There are several techniques and approaches for incisional hernia repair but no single method was proved as gold standard. This study was taken to determine the initial outcome of repair of abdominal incisional hernia with component separation technique (CST) also known as abdominal wall reconstruction, reinforced by pre peritoneal mesh placement.Method: This prospective observational study was conducted in Dhaka Medical College Hospital, Dhaka & Bangladesh Medical College Hospital, Dhaka over 6 months between 12th august 2014 to 11 February 2015. Based on predefined enrollment criteria, a total of 20 cases of incisional hernia were consecutively included in this study. The outcome variables were wound infection, seroma or hematoma formation, abdominal discomfort, gut obstruction.Result: The study showed that mean age of the patients was 42.3 years (range: 19 59 years). Females were more likely to be affected than males (3:1). Overweight or obesity was found in 25 % cases. Bulging at the site of scar was the main sign of incisional hernia (90 %). One-third (35%) of the patients gave the history of constipation and (20%) had surgical site infection (SSI) after previous operation. Some (10%) had chronic obstructive pulmonary diseases (COPD). All the cases were primary. Over one— third of the patients( 35%) complained of pain after operation. About two-third( 65%) patients had no pain. Other reported complication was seroma.Conclusion: The study concluded that the CST reinforced by pre-peritoneal mesh placement provides good initial outcome in the repair of large midline incisional hernia.Journal of Surgical Sciences (2021)Vol. 25(2) : 3-7